Wages and earnings - Dean, Andrew (Reviews of United Kingdom statistical sources, 1980)
Wages and Earnings is a review of statistical sources, both official and non-official, on wages and earnings in Britain. The non-official sources of data relate mostly to salary statistics, while most of the official data are produced by the Department of Employment. Topics covered range from wage rates and salary scales to fringe benefits and labor costs. The concepts of incomes, earnings, wages, and salaries are also explained. This book is comprised of eight chapters and begins with an overview of earnings as well as the concepts of wages and salaries. The next chapter examines three offi.